1996
DOI: 10.1017/s0890037x00040549
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Weeds with Phytopathogenic Bacteria

Abstract: Until recently, phytopathogenic bacteria have not been considered potential biological weed control candidates because they lack the ability to penetrate intact plants. This deficiency can be overcome by providing entry wounds or using surfactants. Spray application ofPseudomonas syringaepv.tagetis(5 × 108cells/ml) in aqueous buffer with a surfactant produced severe disease in Canada thistle, common ragweed, Jerusalem artichoke, sunflower, and certain other members of the Compositae under field conditions. Spr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 15 publications
(4 reference statements)
0
59
0
1
Order By: Relevance
“…Pathogenic bacteria Xanthomonas campestris pv poannua and P. syringae pv tagetis have been developed as bioherbicides to control annual bluegrass (Poa annua) and Asteraceae weeds, respectively [25]. The phytotoxin produced from a crude extract of Pseudomonas syringae reduced root and shoot growth of weeds in newly-established "Stevens" cranberry bogs [26].…”
Section: Bioherbicides From Pathogensmentioning
confidence: 99%
See 1 more Smart Citation
“…Pathogenic bacteria Xanthomonas campestris pv poannua and P. syringae pv tagetis have been developed as bioherbicides to control annual bluegrass (Poa annua) and Asteraceae weeds, respectively [25]. The phytotoxin produced from a crude extract of Pseudomonas syringae reduced root and shoot growth of weeds in newly-established "Stevens" cranberry bogs [26].…”
Section: Bioherbicides From Pathogensmentioning
confidence: 99%
“…Chandramohan and Charudattan (2003) [76] also found that a mixture of three pathogens, Drechslera gigantia, Exserohilum longirostratum, and Exserohilum rostratum, successfully suppressed the growth of seven weeds in citrus groves in Florida. Amendment of bacterial pathogen aqueous suspensions with surfactants has been studied for helping bacteria efficiently invade plant leaves and broaden host range [25]. Types of formulations using emulsions, organosilicone surfactants, and hydrophilic polymers have advantages and disadvantages in enhancing the efficacy of biotic agents and ease of application [69].…”
Section: Factors Affecting the Efficacy Of Bioherbicidementioning
confidence: 99%
“…A Pseudomonas syringae isolate has been registered to control Canada thistle (Johnson et al, 1996). Other Pseudomonas syringae phytotoxins include: coronatine, syringomycin, syringopeptin, tabtoxin, phaseolotoxin, and tagetetoxin (Table 6).…”
Section: Bacterial Compoundsmentioning
confidence: 99%
“…poannua was shown to control annual bluegrass (Poa annua L.) in bermudagrass ( Table-2) (Johnson, 1994;Johnson et al, 1996). The bacterial agent causes systemic wilting, yellowing and death of the grass and the host-range of this pathovar is restricted to P. annua ssp.…”
Section: Foliar Bacterial Agentsmentioning
confidence: 99%
“…tagetis is being pursued as a possible bioherbicide for Canada thistle (Cirsium arvense L.) control in soybean (Table 2) (Johnson et al, 1995). The bacterium was first reported on marigold, sunflower, common ragweed, and Jerusalem bacterium was first reported on marigold, sunflower, common ragweed, and Jerusalem artichoke and causes apical chlorosis of Canada thistle (Johnson and Wyse, 1991;Johnson et al, 1996). Application of the bacterium in the spring reduced the number of Canada thistle stems/m 2 by 78%, compared to the controls, and no disease occurred on soybean.…”
Section: Foliar Bacterial Agentsmentioning
confidence: 99%